'Gente Borgia'. Un nuevo ejemplo del mecenazgo de los Borja: Primeras inscripciones humanísticas en Valencia. - PONS ALÓS, VICENTE (Scripta, 2019)
Writing and heraldry become a fundamental language to the institutional and personal service of the Borjas. They did not only used in Italy but also in their city of origin and their manors. Both in Xàtiva and Gandía we find the first humanistic inscriptions located in Valencian territory In both cases they are pieces linked to the Borja family and the two are found in the collegiate area of these two cities: in the chapel dedicated to the Mare de Déu de les Febres, a Roman dedication, whose construction was ordered in 1497 by Francesc de Borja, pontifical treasurer, bishop of Teano, later archbishop of Cosenza and cardinal appointed by Alexander VI; and outside of the church of Santa María de Gandía, erected as collegiate in 1499 by Alejandro VI, on both sides of the door of the Apostles, built under the auspices of María Enríquez, widow successively of Pere Lluís de Borja and Joan de Borja, brothers, I and II Borja dukes of Gandía. The duchess widow resumed the unfinished project of the collegiate church that will be finished, as indicated by the inscriptions, in 1500, under his patronage and that of his son Joan, III Borja Duke.